Scenario detection for autonomous vehicle - Zhang, Wei (2019)
With the development of autonomous vehicles, the importance of scenario detection is becoming more and more significant. This project focus on the scenario detection of pedestrians about whether the pedestrians are crossing the road based on scene detection in images. The whole project mainly includes three parts: lane lines detection, object detection and scenario detection of pedestrians.